Wireless power transfer for low power device using magnetic resonant coil
The power is transferred wirelessly through a magnetic resonant coil as an antenna to transmit and receive the energy. This method no longer need complicated with the cable passing around us, with wireless electricity we can charge and make wireless electricity as an input source for electronic equipment such as Handphone, MP3 Player, everything works as a battery source or electrical wiring. The components used to build wireless power transfer can be divided into 4 parts components, transmitter section will convert Direct Current (DC) voltage to Alternating Current (AC) form then receiver will convert AC to DC form that compatible for low power device. Whereas, at receiver section containing with receiver planar coil, receiver rectifier circuit, voltage regulator Integrated Circuit (IC) and mobile phone battery. The DC source that connected to transmitter was provided by the DC source regulator which voltage and current can be adjusted separately. The transmitter coil is function to converts the DC power from an oscillator to a high frequency AC power signal. This high frequency alternating current, which is linked with the wireless power transmitting coil, would create an alternating magnetic field in the coil due to magnetic resonant to transmit energy. In the wireless power charger receiver section, the receiver coils receives that energy as an induced alternating voltage due to resonant coil in its coil and a rectifier in the wireless power receiver section converts that AC voltage to a DC voltage. Rectified DC voltage would be feed to the load through a voltage controller section. That is, the wireless mobile battery charger receiver section main function is to charge a power mobile battery through magnetic resonant coil. From the overall experiment conducted from various design transmitter and receiver circuit using transistor and mosfet, diameter, size and type of materials of magnetic resonant coil. These factors are the norms and necessary aspect of wireless power transfer for mobile phone charger. From the transmitter circuit design using transistor and mosfet test for wireless power transfer by using magnetic resonant coil, it shows that the mosfet IRFP450 has the highest efficiency comparing to mosfet IRFZ44N, transistors BC639 and BD139. The receiver circuit design using full bridge rectifier has the better output DC comparing to half bridge rectifier.